Amyand’s hernia complicated with cecal necrosis: presentation of a case and surgical treatment - Martínez-Martínez, Humberto Gustavo; Pulido-López, Ricardo Alberto; Flores-Ávila, Jaime Enrique; Manzano-Tamez, Marcela; Núñez-Chiriboga, Dafhne Patricia (International Surgery Journal, 2023)
The presence of the vermiform appendix, inflamed or not, within a hernial sac is known as Amyand’s hernia (AH). This represents 1 percent of all inguinal hernias and one third of these are associated with acute appendicitis. This presentation is a rare entity and most of the times it presents as a finding during the surgical event. We report a male patient in his fifth decade of life who consulted for a 10-day history of increased volume in the right inguinal region associated with pain and inability to reduce. An exploratory laparotomy was performed that required a right hemicolectomy. AH represents a diagnostic challenge, in most cases it is considered an incidental intraoperative diagnosis. There is no protocolized treatment, however, the inflammatory degree of the appendix is ​​what will guide the surgical approach.